Cyclic threshold shear strain for pore water pressure generation and stiffness degradation in marine clays at Yangtze estuary - Xiao, Xing; Ji, Dong-Wei; Hang, Tian-Zhu; Cai, Zi-Yang; Zhang, Lei; Wu, Qi; Chen, Guo-Xing (Frontiers in Marine Science, 2023)
Cyclic threshold shear strain is a fundamental property of saturated soils under cyclic loading. To investigate the cyclic threshold shear strain for pore water pressure generation (γtp) and stiffness degradation (γtd), a series of strain-controlled multistage undrained cyclic triaxial tests were carried out on in-situ saturated marine clay in the Yangtze estuary with different plasticity index Ip. The test results show that both γtp and γtd increase with increasing Ip, and γtp is larger than γtd for the same marine clay tested under the same conditions, with γtp = 0.017 ~ 0.019%, γtd = 0.008 ~ 0.012% for Ip of 17, γtp = 0.033 ~ 0.039%, γtd = 0.020 ~ 0.025% for Ip of 32, and γtp = 0.040 ~ 0.048%, γtd = 0.031 ~ 0.036% for Ip of 40. Moreover, the development of stiffness degradation may not necessarily require the generation of pore water pressure but can be aggravated by it. Furthermore, the γtp and γtd of marine clay are compared with terrestrial soils and marine clays cited from the published literature, the results indicate that the special marine sedimentary environment and the combined action of flow and tidal wave system cause the γtp and γtd of marine clay in the Yangtze estuary to be smaller than that of the terrestrial clays and marine clays in other sea areas.